Climate Change Anxiety in Secondary Schools: Results From a Quantitative Study in Germany - Höhnle, Steffen; Velling, Hanna; Schubert, Jan Christoph (Journal of Geography Education, 2024)
The results of a quantitative questionnaire study in cross-sectional design (n = 10.356) at all types of secondary schools in Bavaria presented in the article show that climate change anxiety is on average in the middle range of the rating scale and shows considerable variation. Girls report higher levels than boys, grammar school students moderately higher levels than secondary modern school students, who in turn report higher levels than lower-level secondary school students. At grammar schools a slightly higher discrepancy between girls and boys can be noticed. There are no significant differences between students from urban and rural areas. The stronger the perception of the impact at home, the higher the levels of anxiety. Students who have already been involved in nature or environmental protection groups show higher levels of climate change anxiety.